Perovskite foams used in combination with dense ceramic membranes for oxygen transport membrane applications. Issue 16 (November 2018) - Geffroy, P.-M.; Vivet, A.; Guironnet, L.; Richet, N.; Rossignol, F.; Chartier, T.
Abstract: The future industrial implementation of membranes for oxygen transport requires new designs to increase oxygen semi-permeation, together with robust performance under operating conditions. This work describes the development of innovative membrane designs based on perovskite foams with a very large porosity (above 90%) supporting thin dense perovskite membranes (thickness of 50–100 µm). The preparation of such foam-supported membranes is described in this paper. The performances in terms of oxygen semi-permeation are also measured and compared with the best results reported in the literature up to date.